Đáp án:
Giải thích các bước giải: Điều kiện của $x$: $x \neq \pm 1$
a) $A=(\frac{x+1}{x-1}-\frac{x-1}{x+1} ):(\frac{2}{x^2-1}-\frac{x}{x-1}+\frac{1}{x+1})$ $\\$$=\frac{(x+1)^2-(x-1)^2}{(x+1)(x-1)}:\frac{2-x(x+1)+x-1}{(x+1)(x-1)}$
$\\$$=\frac{4x}{(x+1)(x-1)}:\frac{1-x^2}{(x+1)(x-1)}$
$\\$$=\frac{4x}{1-x^2}$
b) $A=\frac{1}{2}$
$\Leftrightarrow \frac{4x}{1-x^2}= \frac{1}{2}$
$\Leftrightarrow 8x=1-x^2$
$\Leftrightarrow x^2+8x-1=0$
$\Leftrightarrow (x+4)^2=17$
$\Leftrightarrow x+4=\pm \sqrt{17}$
$\Leftrightarrow x=-4 \pm \sqrt{17}$